Pendekatan Individual melalui Case Work: Studi Intervensi Sosial terhadap Anak dengan Masalah Kepercayaan Diri dan Perundungan - Sabila, Nazwa; Triani, Emi (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The Field Practice Internship (FPI) is a form of contextual learning designed to develop the competencies of Social Welfare students through direct hands-on experience in the field. This activity aims to integrate theoretical knowledge acquired during coursework with practical applications in various social institutions, as well as to enhance skills in social analysis, interpersonal communication, and the formulation of targeted social interventions. During the FPI, students are placed in diverse social service institutions such as social care centers, non-governmental organizations, and social service offices, where they observe, participate, and contribute to ongoing social services. The results from the internship indicate that direct engagement in the field significantly strengthens students' understanding of the dynamics of social issues and the strategies for addressing them. Moreover, the FPI serves as a critical reflective platform for appreciating the role of social workers in advocating for community welfare. Hence, the field practice internship not only serves as a valuable learning platform but also helps in shaping the professional character of future social workers.